The adrenergic-regulated CRTC1 and CRTC2 phosphorylation and cellular distribution is independent of endogenous SIK1 in the male rat pinealocyte. (15th October 2015) - McTague, J.; Ferguson, M.; Chik, C.L.; Ho, A.K.
Abstract: Salt inducible kinase 1 (SIK1) has been reported to repress cAMP-response element binding protein (CREB)-mediated gene transcription by causing the nuclear export of CREB-regulated transcription coactivators (CRTCs) through phosphorylation. Although the repressor role of SIK1 in suppressing the expression of arylalkylamine N-acetyltransferase, the enzyme that controls the daily rhythm in melatonin production in the rat pineal gland, has been established, whether SIK1 regulates the phosphorylation and localization of CRTC1 and CRTC2 in this tissue remains unclear. The present study found that overexpressing SIK1 in NE-stimulated rat pinealocytes could increase the phosphorylation of CRTC1 and CRTC2, reduced selectively the nuclear level of CRTC2 (but not that of CRTC1), and elevated the cytosolic levels of both CRTC1 and CRTC2. In contrast, transient knockdown of endogenous SIK1 had no effect on the phosphorylation or distribution of CRTC1 and CRTC2 in norepinephrine (NE)-stimulated pinealocytes. Our results also showed that adrenergic blockade during NE stimulation led to a rapid rephosphorylation and decline in the nucleus levels of CRTC1 and CRTC2; however SIK1 knockdown had no effect on this rapid rephosphorylation. Moreover, studies with kinase inhibitors revealed that kinase(s) sensitive to KT5823 appeared to be involved in this rapid rephosphorylation. Together, these results indicate that although overexpressing SIK1 can phosphorylate CRTC1 and CRTC2 in the NE-stimulated pinealocyte, the endogenous SIK1, in spite of its induction by NE, does not appear to be the main regulator of the phosphorylation and intracellular localization of these two coactivators. Highlights: Overexpressing SIK1 can phosphorylate CRTC1 and CRTC2 in NE-stimulated pinealocytes. SIK1 repression of NE-stimulated AANAT is independent of phosphorylation of CRTCs. Endogenous SIK1 does not regulate the phosphorylation and localization of CRTCs. These results challenge how SIK1 acts to repress gene expression.